METODE DAN PENDEKATAN TEORITIS DALAM DERIVASI BATIMETRI LAUT DANGKAL DARI DATA CITRA SATELIT WORLDVIEW-2 - Roem, Muhammad (Jurnal Harpodon Borneo, 2011)
WorldView-2 sensor, which was launched in October 2009 represents a new achievement in geographic information systems, especially in the marine field. Differences WorldView-2 sensor with sensor-owned satellite that has gone before is located on four new band that has the coastal band, yellow band, red edge band, and near-IR 2 band. Coastal band sensors are specifically designed for applications in the littoral zone or shallow sea. This is very helpful in mapping the depth or bathymetry. This is not only important for navigational purposes but also in seeing the shipping processes of coastal disaster mitigation planning and even in coastal areas such as tsunami and storm surge. This paper gives an overview of how the application of WorldView-2 imagery for mapping shallow sea bathymetry can be done based on methods and approaches that has been already available for the other sensor. Keywords : WorldView-2, Coastal Band, Bathymetry, Shallow Marine